Ranking the unwritten rules of the social game we all play - Érdi, Péter 1946- (Oxford University Press, 2020)
"We like to see who is stronger, richer, better, or cleverer. Since we humans (1) love lists, (2) are competitive, and (3) are jealous of other people, we like ranking. We can rank some situations objectively: students ranked by their heights reflects objectivity. However, many "Top Ten" (or twenty-one, thirty-three, etc) lists are based on subjective categorization and give only the illusion of objectivity. In fact, we don't always want to be seen objectively since we don't mind having a better image or rank than deserved. The book applies scientific theories to everyday experience by raising and answering questions like: Are college ranking lists objective? How do we rank and rate countries based on their fragility, level of corruption, or even happiness? How do we find the most relevant web pages? How employees are ranked? The book is offered to people whose neighbor has a fancier car; employees, who are being ranked by their supervisors; managers, who are involved in ranking but may have qualms about the process; businessmen interested in creating better visibility for their companies; scientists, writers, artists, and other competitors who would like to see themselves at the top of a success list; college students who are just preparing to enter a new phase of social competition. The Reader will engage in an intellectual adventure to better understand the difficulties of navigating between objectivity and subjectivity and to better identify and modify her place in real and virtual communities by combining human and computational intelligence. ranking, rating, metrics, comparison, list, objective, subjective, manipulation, reputation, recommendation systems"--
Keywords: Subjektivität; Ranking; Bewertung; Rating; Manipulation; Objektivität; Wettbewerb; Soziale Schichtung; Gesellschaft; Social stratification; Competition / Social aspects; Social comparison